Participatory Modeling With QUICKScan to Shape Sustainable Urban Development - Verweij, Peter; Cormont, Anouk; Eupen, Michiel van; Winograd, Manuel; Hardoy, Jorgelina (Frontiers in Environmental Science, 2020)
Current spatial planning methods are often technocratic, slow, fail to use the right kind of evidence or do not involve (all) the actors needed to create support and consensus. We present a method that facilitates the use of evidence (data) in spatial planning processes, resulting in a joint understanding of the most important interactions in a participatory setting, as a way of capacity building across actors. QUICKScan is a participatory modelling method that links stakeholder- and decision maker knowledge and preferences to available spatial and spatio-statistical data, designed for group use in a multi-stakeholder workshop setting. We describe four urban QUICKScan applications, that vary in objective, scale and institutional setting. The most critical in organising a QUICKScan session is to: i) include crucial participants (decision maker, local data expert and local thematic experts) in a single plenary workshop, ii) create an open atmosphere in which each and everyone’s opinion is treated equally, iii) dialogue is more important than an abundance of detailed spatial data, and iv) start with simple modelling rules and iterate often while expanding the set of rules and trying out alternatives.